2021
DOI: 10.1021/acs.nanolett.1c00865
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and Protection of Skyrmions by Patterns of Modified Magnetic Properties

Abstract: Magnetic skyrmions are versatile topological excitations that can be used as nonvolatile information carriers. The confinement of skyrmions in channels is fundamental for any application based on the accumulation and transport of skyrmions. Here, we report a method that allows effective position control of skyrmions in designed channels by engineered energy barriers and wells, which is realized in a magnetic multilayer film by harnessing the boundaries of patterns with modified magnetic properties. We experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…However, these attributes can usually only be changed for the entire layer or device. The ability to locally control these magnetic parameters could greatly enhance the functionality of skyrmion based devices [25][26][27][28], or devices that use other types of chiral textures. Enabling the creation of regions with high and low energy that could then be used to pin, guide [25][26][27][28], or nucleate [17,29,30] such textures at desired locations in the device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these attributes can usually only be changed for the entire layer or device. The ability to locally control these magnetic parameters could greatly enhance the functionality of skyrmion based devices [25][26][27][28], or devices that use other types of chiral textures. Enabling the creation of regions with high and low energy that could then be used to pin, guide [25][26][27][28], or nucleate [17,29,30] such textures at desired locations in the device.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to locally control these magnetic parameters could greatly enhance the functionality of skyrmion based devices [25][26][27][28], or devices that use other types of chiral textures. Enabling the creation of regions with high and low energy that could then be used to pin, guide [25][26][27][28], or nucleate [17,29,30] such textures at desired locations in the device. It has already been well established that Ga + and other types of ion irradiation can be used to locally tune the magnetic parameters of single magnetic layers in areas as small as 40 nm [31][32][33][34], but its effect on magnetic multilayers is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, several experimental reports demonstrated that the perpendicular magnetic anisotropy (PMA) in a magnetic substrate hosting skyrmions could be modified locally in a precise manner [32,33], which could be an effective method for constructing an artificial pinning landscape. The artificial pinning landscape can be used to confine and protect skyrmions [32,33] and, meanwhile, may affect the static and dynamic properties of skyrmions [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…By using helium ion beam, the DM interaction in a localized region was modified to confine skyrmions in simple geometric shapes like nano-strips and squares [29]. Recently, it was demonstrated that skyrmions can be effectively confined in channels by fabricating stripes with modified magnetic properties in a single ferromagnetic film [30]. Alternatively, Zhang et al [31] showed that skyrmions were directly created by scanning the surface of a specimen by a magnetic force microscopy (MFM) tip with bias field.…”
Section: Introductionmentioning
confidence: 99%